Dutch healthcare reform: did it result in performance improvement of health plans? A comparison of consumer experiences over time - Rademakers Jany; Spreeuwenberg Peter; Hendriks Michelle; Delnoij Diana MJ (BMC, 2009)
Abstract Background Many countries have introduced elements of managed competition in their healthcare system with the aim to accomplish more efficient and demand-driven health care. Simultaneously, generating and reporting of comparative healthcare information has become an important quality-improvement instrument. We examined whether the introduction of managed competition in the Dutch healthcare system along with public reporting of quality information was associated with performance improvement in health plans. Methods Experiences of consumers with their health plan were measured in four consecutive years (2005-2008) using the CQI® health plan instrument 'Experiences with Healthcare and Health Insurer'. Data were available of 13,819 respondents (response = 45%) of 30 health plans in 2005, of 8,266 respondents (response = 39%) of 32 health plans in 2006, of 8,088 respondents (response = 34%) of 32 health plans in 2007, and of 7,183 respondents (response = 31%) of 32 health plans in 2008. We performed multilevel regression analyses with three levels: respondent, health plan and year of measurement. Per year and per quality aspect, we estimated health plan means while adjusting for consumers' age, education and self-reported health status. We tested for linear and quadratic time effects using chi-squares. Results The overall performance of health plans increased significantly from 2005 to 2008 on four quality aspects. For three other aspects, we found that the overall performance first declined and then increased from 2006 to 2008, but the performance in 2008 was not better than in 2005. The overall performance of health plans did not improve more often for quality aspects that were identified as important areas of improvement in the first year of measurement. On six out of seven aspects, the performance of health plans that scored below average in 2005 increased more than the performance of health plans that scored average and/or above average in that year. Conclusion We found mixed results concerning the effects of managed competition on the performance of health plans. To determine whether managed competition in the healthcare system leads to quality improvement in health plans, it is important to examine whether and for what reasons health plans initiate improvement efforts.